Endocannabinoid turnover and function - Patel, Annie (2010)
The therapeutic benefits of cannabis have been known for centuries of years. Yet it has only been in the last 40 years that an understanding of the system by which its works in our bodies has begun to be defined. This has in turn led to the discovery and understanding of the endogenous cannabinoid (eCB) system, alongside its main synthesizing and hydrolysing enzymes as well as the endogenous ligands. The use of synthetic cannabinoid receptor (CBR) ligands for therapeutic use has provided problems regarding the natural endogenous regulatory tone of the eCBs, which in turn has resulted in unwanted side effects. Part of the reason of this is due to synthetic agonists producing the well documented psychotropic effects at CB t receptors. Alternative targets for the manipulation of the eCB system for therapeutic benefits have been explored. One remains to be the use of FAAH inhibitors, which in turn potentially increase levels of eCBs in the system, hence potentiating their effects at the CBRs, or at other receptor sites. Therefore we have developed two HTS assays for the identification of potential inhibitors of FAAH and MAGL. They prove to be robust, cheap and facile and provide a clear indication of inhibitable levels of FAAH and MAGL activity. The FAAH assay can be further used to establish concentration-response curves of initial `hit' compounds. Yet, the HTS MAGL assay requires further characterization for use in construction of concentration-response curves, as they are not assays specific for MAGL acitivity and include hydrolysis of the substrate 4-NPA by non-specific esterases. Z-factor scores were calculated for both assays, indicating excellent assays, which can potentially be applied to industrial lab robotics for screening of compound libraries.